PENGARUH LAMA PENGGUNAAN MULSA DAN DOSIS PUPUK KANDANG TERHADAP PERTUMBUHAN CABAI (Capsilum Annum) SEBAGAI BAHAN PENYUSUN PETUNJUK PRAKTIKUM BIOLOGI KELAS XII SMA NEGERI 1 BARAT - Zainal Aripin (UNIVERSITAS PGRI MADIUN, 2016)
Learning biology is one area of Natural Sciences (IPA) which is integral with practical activities. The lab activities are very important in understanding science concepts. One material that requires practical learning activities more meaningful so that the material of plant growth and development of class XII Science. It would require new innovation in the development lab manual. This study aims to make research the effect of duration of use and dose of manure mulchon plant growth chili as the building blocks lab manual.This research was conducted using a